Investigating the Sensitivity of Alfvén Pulse Interactions to Plasma Beta in the Corona - Naser Karimi; Mahdi Alizadeh; Zianab Shajei (Iranian Journal of Astronomy and Astrophysics)
Two competing theories, the wave theory and reconnection theory, provide explanations for solar corona heating, supported by observations of wave phenomena and magnetic reconnection on the Sun. Plasma β, the ratio of thermal plasma pressure to magnetic pressure, varies significantly in the solar corona, influencing wave propagation Throughout much of the corona, the plasma β is considerably smaller than one, to disregard pressure gradients in the plasma. However, plasma β fluctuates throughout the entire region due to the varying magnetic field, such that near null points, the magnetic field diminishes, leading to a potential increase in plasma β. This study focuses on Alfvén pulses interacting with a 2D magnetic null point, investigating the nonlinear effects of plasma beta adjustment in different layers. The study utilizes the PLUTO code, a sophisticated shock-capturing numerical framework, to model the interactions of Alfvén pulses under varying plasma β conditions. The simulations are conducted on high-resolution Cartesian grids with zero-gradient boundary conditions to ensure accuracy. By solving the magnetohydrodynamic (MHD) equations, the analysis reveals temporal fluctuations in the system’s response, with certain instances characterized by higher amplitudes and sharper peaks, indicative of intensified interactions of the Alfvén pulse. The variations in amplitude and peak sharpness underscore the dynamic nature of the system, with certain moments displaying stronger responses than others. On the one hand, when we adjust the plasma beta closer to the null point, the changes in radial velocity and density disturbance decrease, and over time, the wave energy is released more rapidly along the field lines. Density and velocity changes depend on plasma β and proximity to the null point, emphasizing the system’s sensitivity to these parameters. Therefore, it is essential to consider atmospheric conditions for accurate energy transfer assessments.